Are buffers around home representative of physical activity spaces among adults?. (May 2017) - Holliday, Katelyn M.; Howard, Annie Green; Emch, Michael; Rodríguez, Daniel A.; Evenson, Kelly R.
Abstract: Residential buffers are frequently used to assess built environment characteristics relevant to physical activity (PA), yet little is known about how well they represent the spatial areas in which individuals undertake PA. We used System for Observing Play and Recreation in Communities data for 217 adults from five US states who wore an accelerometer and a GPS for three weeks to create newly defined PA-specific activity spaces. These PA spaces were based on PA occurring in bouts of ≥10 min and were defined as 1) the single minimum convex polygon (MCP) containing all of a participant's PA bout minutes and 2) the combination of many MCPs constructed using each PA bout independently. Participants spent a large proportion of their PA bout time outside of 0.5, 1, and 5 mile residential buffers, and these residential buffers were a poor approximation of the spatial areas in which PA bouts occurred. The newly proposed GPS-based PA spaces can be used in future studies in place of the more general concept of activity space to better approximate built environments experienced during PA. Highlights: Adults spend a high proportion of their physical activity time outside of residential buffers. Residential buffers and adult physical activity spaces have poor spatial overlap. Similar studies of other health behaviors may extend findings to other disciplines.